A low-cost active reflector and a passive corner reflector network for assisting landslide monitoring using multi-temporal InSAR. Issue 11 (2nd November 2022) - Luzi, Guido; Barra, Anna; Gao, Qi; F.Espín-López, Pedro; Palamà, Riccardo; Monserrat, Oriol; Crosetto, Michele; Colell, Xavier
ABSTRACT: A C-band Low-cost Active Reflector (AR) has been tested in a real experimental campaign aimed at monitoring through multi-temporal InSAR an area threatened by a landslide that occurred in 2019. To monitor and characterize the movement, a network of eight Passive Corner Reflectors and one Active Reflector were installed along a forested slope. A set of 285 interferograms obtained combining 60 Sentinel-1 SAR images were processed to evaluate the stability of the area. The AR, installed in a stable location close to the landslide, was used to provide a reference point in this low coherence area. Despite the high sensitivity of the phase response of such devices to temperature changes, the device operates with a stability of ±2 mm in deformation retrieval, a value acceptable for monitoring purposes, with a moderate range of temperature values.